METHOD VALIDATION FOR DETERMINATION OF ORGANOCHLORINE PESTICIDE RESIDUES IN FOOD AND FEED - Brankica Kartalović; Željko Mihaljev; Nadežda Prica; Sandra Jakšić; Milica Živkov Baloš; Miroslav Ćirković (Archives of Veterinary Medicine, 2016)
Validation of analytical methods ensures the reliability and accuracy of analytical results. To get a reliable result we performed a validation of the method taking into account all factors that may aff ect of the result. In this paper we optimized QuEChERS method for food and feed sample preparation as well as instrumental method using gas chromatography with mass spectrometry (GC-MS), and we obtained a method for successful determination of pesticides with calibration through the matrix. In this way, applying calibration through matrix, we satisfi ed the requirements for precision and reproducibility of the method being less than 20%, the accuracy rate in the range of 70-130% and method linearity throughout the range of interest.